Insights on ownership pattern and demand for machinery in Indian agriculture - KANDPAL, ANKITA; KAR, AMIT; IMMANUELRAJ, KINGSLY; SINGH, ALKA; JHA, GIRISH KUMAR; SINGH, PREMLATA (The Indian Journal of Agricultural Sciences, 2022)
As the wage rate for labour escalates in agriculture, farmers opt for other power alternatives. Mechanization of farms provides an opportunity to overcome the issue of labour scarcity and rising cost of production besides facilitating timely farm operations thereby increasing yield and farmer’s income. An examination of existing level of mechanization across the states in different crops is computed during 2018 using mechanization index for 2001–02 and 2013–14. The study concludes that the extent of mechanization is not uniform across crops and states. Wheat is the most mechanized crop and Punjab shows highest level of mechanization in the farms. The factor demand elasticity estimates confirm that change in market prices of inputs significantly affect the machinery usage in paddy and wheat. Substitution elasticities also indicate substitution between machine labour and human labour in major crops during 1996–2013.